Reproducibility of Standardized Uptake Values Including Volume Metrics Between TOF-PET-MR and TOF-PET-CT - Tanaka, Aruki; Sekine, Tetsuro; ter Voert, Edwin E. G. W.; Zeimpekis, Konstantinos G.; Delso, Gaspar; de Galiza Barbosa, Felipe; Warnock, Geoffrey; Kumita, Shin-ichiro; Veit Haibach, Patrick; Huellner, Martin (Frontiers in Medicine, 2022)
Purpose: To investigate the reproducibility of tracer uptake measurements, including volume metrics, such as metabolic tumor volume (MTV) and tumor lesion glycolysis (TLG) obtained by TOF-PET/CT and TOF-PET/MR. Materials and Methods: Eighty consecutive patients with different oncologic diagnoses underwent TOF-PET/CT (Discovery 690; GE Healthcare) and TOF-PET/MR(SIGNA PET/MR; GE Healthcare) on the same day with single dose -18F-FDG injection. The scan order, PET/CT following or followed by PET/MR, was randomly assigned. A spherical volume of interest (VOI) of 30 mm was placed on the liver in accordance with the PERCIST criteria. For tumor delineation, VOI with a threshold of 40% and 50% of SUVmax was used (VOI40 and VOI50). The SUVmax, SUVmean, SUVpeak, MTV and TLG were calculated. The measurements were compared between the two scanners. Results: In total, 80 tumor lesions from 35 patients were evaluated. There was no statistical difference observed in liver regions, whereas in tumor lesions, SUVmax, SUV mean, and SUVpeak of PET/MR were significantly underestimated (p < 0.001) in both VOI40 and VOI50. Among volume metrics, there was no statistical difference observed except TLG on VOI50 (p = 0.03). There was a moderate correlation of the liver SUV and SUL metrics (r = 0.63-0.78). In tumor lesions, SUVmax and SUVmean had a stronger correlation with underestimation in PET/MR (r = 0.92 and 0.91 with slope = 0.71 and 0.72, respectively). In the evaluation of MTV and TLG, the stronger correlations were observed both on VOI40 (r = 0.75 and 0.92) and VOI50 (r = 0.88 and 0.95). Conclusion: PET metrics on TOF-PET/MR showed a good correlation with that of TOF-PET/CT. SUVmax and SUVpeak of tumor lesions were underestimated by 16% on PET/MRI. MTV with % threshold can be regarded as identical volumetric markers for both TOF-PET/CT and TOF-PET/MR.